ARABIC PERFORMANCE CURRICULLUM DEVELOPMENT: RECONSTRUCTION BASED ON ACTFL AND DOUGLAS BROWN PERSPECTIVE - Hasanah, Mamluatul; Mubaligh, Ahmad; Sari, Risna Rianti; Syarofah, Alfiatus; Prasetyo, Agung (Ijaz Arabi Journal of Arabic Learning, 2021)
The development of the Arabic language performance curriculum in this study is carried out by reconstructing the curriculum design based on ACTFL and Douglas Brown's thoughts. The development model follows the steps set by Jack C. Richard. Needs analysis is carried out by simultaneously combining objective need analysis (questionnaire and interview) with subjective need analysis (review of the ACTFL document and Douglas Brown's thoughts). The results determine that the objectives, teaching materials, learning activities of Arabic language performance learning are arranged by considering three things of necessaries, and lack. The reconstruction results show that the Arabic language performance curriculum is directed at achieving five language performance standards, namely communication, cultures, comparison, communication. And to achieve that, speaking learning activities are designed to be imitative, intensive, responsive, interactive and extensive. Meanwhile, writing skills are at the order of the level of imitative, intensive, responsive, and extensive.